KUALITAS DAN AKUNTABILITAS SUPERVISOR PENDIDIKAN - Muh. Hizbul Muflihin (IAIN Pekalongan, 2009)
The advance of learning for the forthcoming years is beyond doubt indispensable as the consequence of life challenges and society demand in gratifying life need which is getting upsurge – that is being hassled on education. Education issue will absolutely occupies teachers as the ultimate tip in education manoeuvre at schools. Correlating to teachers’ main profession – that is teaching, hence education quality is prearranged as the responsibility of teachers. Nevertheless, their engagements are sometimes unfulfilled in anticipating the demand changes of learners or parents. These conditions are triggered by teachers’ lack of ability in tracking the massive development both in tecnology and information as well - which are getting more complex. At this juncture, the emergence of an educational supervisor is truly decisive in helping them enhancing the quality of teachers’ personality – both in administrative and educational division.